(untitled) (Journal of Parents and Teachers, 2013)
To talk about teachers practice evaluation nowadays assumes to refer to one of the most problematic, controversial and feared ambits by a big portion of the teachers. The intention of the article is to encourage teachers to look towards self-evaluation practices that entail the idea of the evaluation as an aid, growing and personal and professional development whose aim is to help the teacher to discover how he/she can improve his/her professional practice. Only by using evaluation as a resource for investigation and education (because evaluation is a way of learning), the dream of a teachers evaluation as a quality guarantee will come true. In order to start-up this process, this article presents a series of orientations and didactic strategies for its functionality.